2018
DOI: 10.4236/ajc.2018.61001
|View full text |Cite
|
Sign up to set email alerts
|

Media Hype and Its Influence on Athletic Performance

Abstract: A survey of university athletes examined whether uses of four media (newspapers, television, radio or the Internet) for sports information were related to self-perceptions of emotions, motivations and attitudes. The results suggest that newspaper and Internet use reduced feelings of stress among the athletes, perhaps due to athletes' use of the two media as diversions from the pressures of competitive athletics. Television use was not related to any of the measures of athletes' self-perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…The current finding contributes to research that has identified the role social media and networking sites play in mood management (e.g., Heinonen, 2011;Johnson & Knobloch-Westerwick, 2014) by illustrating that athlete exposure to social media during events assist in maintaining a more relaxed state by creating a diversion from competition pressures. The finding extends Frisby and Wanta's (2018) work on Internet application to social media through the identification of mood management as a key driver in creating a diversion from the pressures of competition. Relaxation strategies are an important feature of athletes' psychological preparation for a competition or major sport event (Ungerleider, 2005).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The current finding contributes to research that has identified the role social media and networking sites play in mood management (e.g., Heinonen, 2011;Johnson & Knobloch-Westerwick, 2014) by illustrating that athlete exposure to social media during events assist in maintaining a more relaxed state by creating a diversion from competition pressures. The finding extends Frisby and Wanta's (2018) work on Internet application to social media through the identification of mood management as a key driver in creating a diversion from the pressures of competition. Relaxation strategies are an important feature of athletes' psychological preparation for a competition or major sport event (Ungerleider, 2005).…”
Section: Discussionsupporting
confidence: 58%
“…Although there are several negative aspects associated with social media use, the platforms may also provide some benefits to athletes. For instance, Internet applications and social media can be used as a diversion from competing pressures (Frisby & Wanta, 2018;Hayes et al, 2019). This may be particularly important for athletes who experience feelings of stress during major sport events.…”
Section: Social Media Impacts On Athletesmentioning
confidence: 99%
“…Arai et al (2014) mencionan que la legitimidad extiende la credibilidad de la imagen de una atleta. Se argumenta que la efervescencia de los medios de comunicación tiene un impacto sobre la influencia a corto plazo, sin embargo, perjudica la imagen de la marca del atleta (Frisby y Wanta, 2018). Por ejemplo, el alero de la NBA Kris Humphries se convirtió de un día para otro en la comidilla del pueblo por su matrimonio con Kim Kardashian, pero su popularidad se mantuvo alta por un período muy breve (Pifer et al, 2015).…”
Section: Discussionunclassified
“…Arai et al (2014) mentioned that genuineness extended the credibility of an athlete's image. It is argued that media hype impacts a short-term influence, yet it affected athlete brand image (Frisby & Wanta, 2018). For instance, NBA forward Kris Humphries became the talk of the town overnight because of his marriage to Kim Kardashian, yet his popularity was high for only a short period (Pifer, Mak, Bae, & Zhang, 2015).…”
Section: Discussionmentioning
confidence: 99%